Dialectic and narrative - Flynn, Thomas R.; Judovitz, Dalia (Contemporary studies in philosophy and literature, 1993)
Dialectic and narrative reflect the respective inclinations of philosophy and literature as disciplines that fix one another in a Sartrean gaze, admixing envy with suspicion. Ever since Plato and Aristotle distinguished scientific knowledge (episteme) from opinion (doxa) and valued demonstration through formal final causes over emplotment (mythos), the palm has been awarded to dialectic as the proper instrument of rational discourse, the arbiter of coherence, consistency, and ultimately of truth. The matter becomes more complicated when we recognize the various uses of the term "dialectic" in the tradition, some of which complement and even overlap the narrative domain. By confronting these concepts with one another, either de facto or ex professo, the following essays not only raise anew the ancient questions of the identities of philosophy and literature, but do so in the context of recent "postmodern" challenges to their relative autonomy. -- Back cover